TWO TEACHERS IN ONE GROUP: DOUBLE PROBLEM OR DOUBLE SUCCESS? - Juraeva Maftuna Bakhtiyor qizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
This article suggests collaborative learning often occurs in inclusive groups. In a co-teaching group, teachers work together to plan lessons, teach, monitor student progress, and manage the group.